GEOGRAPHIC INFORMATION SYSTEM APPLICATION FOR TRADITIONAL MARKET MAPPING IN PADANG CITY BASED ON ANDROID - Melladia Melladia; Fadila Afriansyah (Smart Education, 2025)
This study aims to develop an Android-based Geographic Information System (GIS) application for mapping traditional markets in Padang City. The main issue addressed is the lack of accessible spatial information regarding market locations for the general public. The research employed field observations, interviews with the Trade Office and market vendors, and literature study. The system development followed the waterfall model, comprising requirement analysis, system design, implementation, testing, and maintenance. The application was built using Android Studio, LeafletJS, and QGIS. The results show that the application successfully presents market location information in an interactive map format, displays detailed market data, and facilitates administrative data management. This application is expected to assist users in locating traditional markets and support local government efforts in spatial data management more efficiently.Keyword: Georaphic Information System, Padang City, QGIS, Leaflet, Android